The state of social insurance for agricultural workers in the Near East and North Africa and challenges for expansion - Lucas Sato (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
Agricultural workers are exposed to many risks during their life cycle and are particularly vulnerable to covariate risks, such as droughts, armed conflict and pandemics. Despite the great potential of social protection policies to protect this segment of the population, agricultural workers are commonly excluded from social protection systems - especially from contributory schemes - due to legal, programme design, financial, administrative, institutional, participation, and information barriers. This paper analyses the availability of social insurance schemes for agricultural workers in the Near East and North Africa (NENA) region, including many types of insurance: old age, disability and survivors', sickness and maternity, work injury, and unemployment, as well as family and child allowances. In addition, we analyse agricultural insurance schemes, as they play a critical role in protecting agricultural producers from the catastrophic impact of covariate risks. We examine the barriers for agricultural workers to participate in contributory schemes, highlighting good practices being adopted in NENA countries to address them. This paper thus aims to help fill a gap in the literature regarding the role of contributory schemes for agricultural workers. Most importantly, it aims to highlight paths towards more comprehensive social protection systems, capable of addressing the pressing challenges in NENA countries, such as inequities between rural and urban populations, lack of rural development, and insufficient protection for rural families.
Keywords: 330; social protection; social insurance; rural development; agricultural workers; Near East and North Africa